Investigate the Friction Drilling of Aluminium Alloys According to the Thermal Conductivity - Ozek, Cebeli; Demir, Zulkuf (Assoc Information Communication Technology Education & Science, 2013)
Friction drilling is non-traditional hole drilling method which uses the frictional heat due to the friction between a rotating conical tool and the workpiece to soften and penetrate the work-material and obtained a hole in a thin wall thickness material and at the result a bushing form. The selected spindle speeds were 1200rpm, 1800rpm, 2400rpm, 3000rpm, 3600rpm, and 4200rpm, feed rates were 25mm/min, 50mm/min, 75mm/min, and and 100mm/min. Tool material was HSS which has 36 degrees conical angle and 16mm cylindrical region length, workpiece materials were A1050, A6061, A5083, and A7075-T651 aluminium alloys which have different thermal conductivity coefficients and 4mm thickness. It was investigated the generated frictional heat, surface roughness, and bushing height according to spindle speeds, feed rates, and thermal conductivity coefficient of the materials. At the end it was discovered that with increasing thermal conductivity coefficients, the sufficient frictional heat was gained at the high spindle speeds and low feed rates. The greater bushing heights were obtained at lower spindle speeds and high feed rates. In friction drilling A5083, A6061, and A7075-T651 aluminium alloys, the optimum surface roughness were generated at 2400rpm and all of feed rates, which were used, the optimum surface roughness values were provided. Due to the high thermal conductivity coefficient of A1050 aluminium alloy the optimum surface roughness values were gained at 25mm/min and 2400rpm, at 50mm/min and 3000rpm, at 75mm/min and 3600rpm, 100m/min and 4200rpm feed rate and spindle speed couples.
Keywords: Friction Drilling; Thermal Conductivity; Surface Roughness; Bushing Height